Varietal veridicy in Hittite s-etyma - Puhvel, Jaan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
Hittite lexemes spelled with initial s-signs are etymologically varied and elusive. There are expectably numerous conclusive instances of prevocalic s- harking back to the basic Indo-European sibilant phoneme *s, even as to Sigmund Freud a cigar could indeed be just a cigar. Other cases are less straightforward, evincing a disparate, more complex historical reality, somewhat as for René Magritte an image of a pipe was not a pipe, rather a reflection of a secondary ontic relationship. Attendant ambiguity affords a philologer a wider range of speculation, of plumbing possibilities beyond the obvious or predictable. A century and a half ago pioneering scholars unlocked the phonological DNA of Ancient Greek, raising its etymology to a higher level. After a full century, Hittitology is still short of such attainment, due in part to the refractory nature of the corpus, but in large measure to incomprehensions and incompatibilities of textual and theoretical scholars. Redress of this drawback is a prime desideratum.